(3TQM GdafGQj Ydi EjSGZhLj GdahGFO GdafGQjIs - (3GdafGQj (B( (3GdaQfj (B)(3, GdQhej, TeS GdOjf, eMeO Hf MeRI Hf eMeO, J (B834 (3g`s ((3Ydj Hf MSfs)
(3ChdgG (B:s
... (3bhdg ef MjK faYgG aj GdEjUGd GdXQa CeG eJYdb HHMJ Cj jHMK YfgG HSHH faYgG aj GdEjUGd G HGdEYQGV HGYJHGQ GdeYfi Cj GddhGMb ef MjK faYgG EdN , hGdVejQ QGLY Edi GdJUhQGJ hGdJUOjbGJ dG Edi GdCYQGV (B...s
(3BNQgG (B:s
(3hGdTYQ bjGS eDda ef ebOeGJ JfHSW efgG GdfaS fMh GdNeQ jGbhJI SjGdI Ch JfbHV GdYSd LQI eYhgI hGdeZGdWI bjGS eDda ef ebOeGJ THjgI HGdMb hdG jchf MbG hJSei SaSWI JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6/110s
(3cTa GdXfhf (B1/207s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs